2010
DOI: 10.4141/cjps10075
|View full text |Cite
|
Sign up to set email alerts
|

Control of volunteer adzuki bean (Vigna angularis) with pre- and postemergence herbicides in corn (Zea mays)

Abstract: . 2010. Control of volunteer adzuki bean (Vigna angularis) with pre-and postemergence herbicides in corn (Zea mays). Can. J. Plant Sci. 90: 925Á932. Volunteer adzuki bean within a corn crop can decrease corn yield and increase the adzuki bean seed bank. The objective of this research was to evaluate the efficacy of various preemergence (PRE) and postemergence (POST) herbicides for the control of volunteer adzuki bean [Vigna angularis (Willd.) Ohwi & Ohashi] in corn. Trials were conducted at two locations in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Adzuki bean seeds are also consumed as sprouts because of their soft and crispy texture and attractive fragrance. However, the seed coat of the adzuki bean is hard when compared to other legumes [4]. This hard seed coat characteristic is linked to the polyphenols and suberin compounds accumulated in the palisade layer of seed coat, which reduces water permeability [5].…”
Section: Introductionmentioning
confidence: 99%
“…Adzuki bean seeds are also consumed as sprouts because of their soft and crispy texture and attractive fragrance. However, the seed coat of the adzuki bean is hard when compared to other legumes [4]. This hard seed coat characteristic is linked to the polyphenols and suberin compounds accumulated in the palisade layer of seed coat, which reduces water permeability [5].…”
Section: Introductionmentioning
confidence: 99%
“…ha −1 ) provided up to 95% volunteer adzuki bean control, as low as 38% and 3% control was observed at 8 WAA, respectively, indicating a high degree of variability. Kramer et al (2010) also found that dicamba and (or) atrazine (1800 g a.i. ha −1 ) applied POST provided consistently excellent (≥95%) control of volunteer adzuki bean at 4 and 8 WAA.…”
Section: Control Of Volunteer Adzuki Beanmentioning
confidence: 86%
“…Adzuki bean seed shatter losses from natural causes and during harvest operations have the potential to form a persistent seedbank in the soil. In corn production, volunteer adzuki bean can reduce yield by up to 43% (Kramer et al 2010). Volunteer populations are particularly disadvantageous for soybean growers as adzuki bean seeds vary only slightly in size and are thus difficult to remove from the harvested product (Duke 2012;Kramer et al 2012).…”
Section: Control Of Volunteer Adzuki Beanmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, similar seed hydration patterns were also found in the control seeds (Figure 4). The observed slow initial water uptake was possibly related to the hard seed coat characteristic of the adzuki bean seeds [38]. Once the seed coat is hydrated to some extent (e.g., soaking the seeds in running water for 16 h), its resistance to the water flow may decrease, then the water uptake rate may progressively increase [37].…”
Section: Seed Treatment Effects On Seed Hydrationmentioning
confidence: 98%